Spontaneous rupture of the esophagus: contribution to the national casuistry - Loef, Marcos; Bonilla, Nebel (Cirugía del Uruguay, 2020)
The 4th. case of spontaneous rupture of the esophagus reported in Uruguay is presented. This is the first patient with an early diagnosis, 7 hours after the onset of the clinical symptomatology. This surgery was rendered possible within what is classically regarded as the useful 12 hours span ( this patient was operated on within 7 hours). Conventional positive diagnosis was substantiated by a good anamnesis, phisical examination and above all, a chest X ray which, toghther with the thoracocentesis, confirmed the condition. From the above, the following conclusions are inferable: in the presence of a patient with an acute abdominal or retrosternal picture, accompanied by a state of severe, persistent collapse, unamenable to medication, serial X ray studies of the abdomen and chest (front, profile and oblique) are necessary in arder to detect the early signs of this most severe condiction.